2006
DOI: 10.2151/jmsj.84.939
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Size Changes of Asian Dust Particles Caused by Sea Salt and Sulfate

Abstract: Atmospheric particles were collected in southwestern Japan during dust storm events in spring 2000, and the samples were treated with water-dialysis. In this study, size change of dust particles before and after dialysis is discussed with respect to their sea salt and sulfur contents. It is confirmed that size increase of dust particles has a strong correlation with their sea salt content but is independent from their non-sea-salt sulfur content. This suggests that the growth of dust particles in size during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…To obtain the growth of dust particles due to sea salt adhering, a linear relation between the relative growth of dust particles and their mixture degree, RelativeGrowth = 0.4198 MixtureDegree − 0.0432 with the confidence R 2 = 0.9321, is applied; where the RelativeGrowth of a particle is defined as the ratio of its growth due to sea salt to its diameter and the MixtureDegree of a particle is defined as the ratio of the relative mass of sodium and chlorine to that of sodium, chlorine, aluminium, silicon and iron in the particle. This relation was derived from the data published in a previous paper (Zhang and Iwasaka, 2006).…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…To obtain the growth of dust particles due to sea salt adhering, a linear relation between the relative growth of dust particles and their mixture degree, RelativeGrowth = 0.4198 MixtureDegree − 0.0432 with the confidence R 2 = 0.9321, is applied; where the RelativeGrowth of a particle is defined as the ratio of its growth due to sea salt to its diameter and the MixtureDegree of a particle is defined as the ratio of the relative mass of sodium and chlorine to that of sodium, chlorine, aluminium, silicon and iron in the particle. This relation was derived from the data published in a previous paper (Zhang and Iwasaka, 2006).…”
Section: Methodssupporting
confidence: 92%
“…The size and density of a particle are two key parameters in determining its settling velocity. Field measurements have shown that sea salt emitted from the ocean could significantly change dust particles and cause the particles to grow in size (Andreae et al, 1986; Zhang and Iwasaka, 2004, 2006). Clearly, this kind of growth can cause changes in the settling velocity of particles, thus modifying dust deposition and making the process of dust settling to the sea surface fundamentally different from that in the continental atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Notice that this is completely different from the sulfate in fine particles (diameter < 1 μ m) which had a higher SO 4 2− /Ca 2+ mass ratio (16.2) and a much higher mass percentage of sulfate (>30%) than the coarse particles in the same case. It has been proven that there were usually a large number of sulfur‐containing calcium‐rich particles in the fine size range in long‐range transported Asian dust plumes [ Matsuki et al , 2005; Zhang and Iwasaka , 2006].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the increasing trends of DDV Fe and DDV Al during the fall/winter months are consistent with marine particle growth during increased humidity and sea salt aerosol production. Over the Pacific, dust particles in the marine boundary layer are commonly observed to form larger aggregates through the collisions with sea‐salt particles and coagulations with N or S pollutants [ Andreae et al , 1986; Zhang et al , 2005; Zhang and Iwasaka , 2006]. Atmospheric factors could include increased turbulence, humidity and sea salt particle burdens as observed at Puerto Rico in the summer that may similarly explain the increasing trend of DDV Fe and DDV Al during the later (fall/winter) seasons at Bermuda as well [ Maring et al , 2003].…”
Section: Discussionmentioning
confidence: 99%